2003
DOI: 10.1074/jbc.m208346200
|View full text |Cite
|
Sign up to set email alerts
|

JPDI, a Novel Endoplasmic Reticulum-resident Protein Containing Both a BiP-interacting J-domain and Thioredoxin-like Motifs

Abstract: Several endoplasmic reticulum (ER)-resident luminalproteins have a characteristic ER retrieval signal, KDEL, or its variants at their C terminus. Our previous work searching EST databases for proteins containing the C-terminal KDEL motif predicted some novel murine proteins, one of which designated JPDI (J-domaincontaining protein disulfide isomerase-like protein) is characterized in this study. The primary structure of JPDI is unique, because in addition to a J-domain motif adjacent to the N-terminal transloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 41 publications
(52 reference statements)
1
62
1
2
Order By: Relevance
“…Surprisingly, mutation of the HPD motif significantly enhanced association of ERdj5 with misfolded SP-C (Supplemental Figure S2A). Further analyses revealed that, in contrast to results of a previous study (Hosoda et al, 2003), the HPD mutation did not alter association of ERdj5 (or ERdj4) with BiP (Supplemental Figure S2C). Therefore, stable complexes of misfolded SP-C, BiP, and ERdj5 formed in the absence of the catalytic activity of ERdj5.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…Surprisingly, mutation of the HPD motif significantly enhanced association of ERdj5 with misfolded SP-C (Supplemental Figure S2A). Further analyses revealed that, in contrast to results of a previous study (Hosoda et al, 2003), the HPD mutation did not alter association of ERdj5 (or ERdj4) with BiP (Supplemental Figure S2C). Therefore, stable complexes of misfolded SP-C, BiP, and ERdj5 formed in the absence of the catalytic activity of ERdj5.…”
Section: Discussioncontrasting
confidence: 53%
“…ERdj5 (DNAJC10/JPDI) is an ER-resident lumenal protein with a canonical C-terminal KDEL retrieval motif, a J domain, and four thioredoxin-like domains (Cunnea et al, 2003;Hosoda et al, 2003). Deletion of the J domain prevented interaction of ERdj5 with both BiP and misfolded SP-C, suggesting that association of ERdj5 with substrate was mediated by BiP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results point to a new functional assignment for p58 IPK in serving as a BiP cochaperone to optimize protein folding homeostasis in the ER. Because p58 IPK represents one among several (at least five others) ER localized Jdomain proteins that interface with BiP (Feldheim et al, 1992;Brightman et al, 1995;Shen et al, 2002;Hosoda et al, 2003;Shen and Hendershot, 2005), its absence would result in an ER lumen that is only modestly compromised in overall folding capacity. The functional consequences of this slightly lower protein maturation capacity would be obscured under all but the most taxing conditions and can explain each of the following phenotypic observations in cells and animals lacking p58 IPK .…”
Section: Discussionmentioning
confidence: 99%